Phantom of the opera (1943) [videorecording (DVD)] - Taylor, Eric, 1897-1952; Hoffenstein, Samuel, 1889-1947; Eddy, Nelson, 1901-1967; Foster, Susanna, 1924-2009; Rains, Claude, 1889-1967; Leroux, Gaston, 1868-1927 (Universal Classic Monsters. Complete 30-Film Collection, 2014)
A spectacular retelling of Gaston Leroux's immortal horror tale stars Claude Rains as the masked phantom of the Paris opera house; a crazed composer who schemes to make a beautiful young soprano, the star of the opera company and wreak revenge on those who stole his music. Nelson Eddy, the heroic baritone, tries to win the affections of Foster as he tracks down the disfigured "monster" who has begun murdering those who resist his mad demands.